Obesity Epidemic: Is Its Impact on Total Joint Arthroplasty Underestimated? An Analysis of National Trends. Issue 7 (July 2017) - George, Jaiben; Klika, Alison K.; Navale, Suparna M.; Newman, Jared M.; Barsoum, Wael K.; Higuera, Carlos A.
Abstract: Background: Obesity is a well‐established risk factor for total joint arthroplasty (TJA) and a number of complications including prosthetic joint infection. The annual changes in the prevalence of obesity among primary, revision, and infected TJA has not been studied at a national level. Given the higher costs of complications of TJA, it is important to understand the association of obesity with the annual trends of revision and infected TJA. Questions/purposes: (1) Is the prevalence of obesity increasing among patients undergoing THA/TKA? (2) Is the prevalence of obesity increasing among patients undergoing revision THA/TKA? (3) Is the prevalence of obesity increasing among patients with infected THA/TKA? Methods: Annual volumes of primary, revision, and infected THA and TKA from 1998 to 2011 were obtained from the Nationwide Inpatient Sample. Using mathematical equations, the prevalence of obesity was estimated from relative risks and national obesity prevalence. National obesity prevalence was obtained from public health sources and the relative risk estimates were obtained from previously published meta‐analyses and population‐based studies. Annual prevalence of obesity was obtained by dividing the number of obese primary/revision/infected procedures in each year by the total number of corresponding procedures in that year. Annual changes in the prevalence of obesity were analyzed using linear regression. Results: The prevalence of obesity is increasing among patients undergoing THA (1998: 60, 264 of 154, 337 [39%], 2011: 160, 241 of 305, 755 [52%], increase of 1.05%/year [confidence interval CI, 0.95%‐1.15%], p < 0.001) and TKA (1998: 143, 681 of 251, 309 [57%], 2011: 448, 712 of 644, 243 [70%], increase of 0.97%/year [CI, 0.87%‐1.07%], p < 0.001). There was an increasing prevalence of obesity with THA revisions (1998: 16, 322 of 34, 139 [48%], 2011: 33, 304 of 54, 453 [61%], increase of 1.04%/year [CI, 0.94%‐1.15%], p < 0.001) and in TKA revisions (1998: 16, 837 of 26, 539 [63%], 2011: 52, 151 of 69, 632 [75%], increase of 0.89%/year [CI, 0.79%‐0.99%], p < 0.001). There was an increasing prevalence of obesity with THA infections (1998: 2068 of 3018 [69%], 2011: 6856 of 8687 [79%], increase of 0.80%/year [CI, 0.71%‐0.89%], p < 0.001) and in TKA infections (1998: 3563 of 4684 [76%], 2011: 14, 178 of 16, 774 [85%], increase of 0.65%/year [CI, 0.57%‐0.73%], p < 0.001). Conclusions: The prevalence of obesity has increased in patients undergoing primary, revision, and infected TJA in United States. The obesity epidemic appears to be related to the growing trends of revision and infection after TJA. With the obesity rates expected to grow further, the revision and infection burden associated with obesity may increase in the future. Level of Evidence: Level II, prognostic study.